2003
DOI: 10.4049/jimmunol.171.11.5795
|View full text |Cite
|
Sign up to set email alerts
|

Increased Severity of Murine Lupus in Female Mice Is Due to Enhanced Expansion of Pathogenic T Cells

Abstract: A strong female predominance is a well-recognized feature of human lupus. The mechanism by which sex influences disease expression and severity is not fully understood. To address this question, we used the parent-into-F1 (p→F1) model of chronic graft-vs-host disease (cGVHD) in which lupus-like humoral autoimmunity and renal disease are induced in normal F1 mice. An advantage of this model is that the pathogenic T cells driving disease (donor strain) can be studied separately from nonspecifically activated T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 28 publications
4
42
0
Order By: Relevance
“…The mechanisms by which sex hormones influence diabetes development in the NOD mice are not fully understood. Interestingly, it has recently been shown that the severity of autoimmune systemic lupus erythematosus in female mice is due to enhanced expansion of pathogenic T cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which sex hormones influence diabetes development in the NOD mice are not fully understood. Interestingly, it has recently been shown that the severity of autoimmune systemic lupus erythematosus in female mice is due to enhanced expansion of pathogenic T cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…SLE disease is maintained throughout life due to the presence of autoreactive/memory T cells (3,12,13). To determine whether the increase in PI3K activity is a consequence of disease (present only in activated/memory cells) or an intrinsic defect in naive T cells prior to autoantigen stimulation, we examined pathway activation in both cell subsets.…”
Section: Resultsmentioning
confidence: 99%
“…In kidney, at advanced disease phases, the mesangial proliferation, vascular collapse, and immune complex deposition result in renal failure (4,11). Deregulation of T cell homeostasis is thus a critical event in SLE; distinct T cell defects have been reported in this disease, including altered TCR signaling, reduced IL-2 production, and COX-2 upregulation (7,(12)(13)(14)(15)(16).…”
Section: S Ystemic Lupus Erythematosus (Sle) Is a Chronic Inflammatormentioning
confidence: 99%
“…This chronic inflammatory process affects ∼1 in 1000 whites, with even higher frequencies in blacks, Native Americans, and Asians (90% of patients are females) (1)(2)(3). Current immunosuppressive therapy based on long-term corticosteroid treatment presents side effects (4,5); it is thus important to develop therapeutic approaches that are more specific.…”
Section: S Ystemic Lupus Erythematosus (Sle) Is a Complex Multigenic mentioning
confidence: 99%